ANALISIS TINGKAT PENCEMARAN POSFAT DAN NITRAT DI BEBERAPA SUB DAS KALIMANTAN SELATAN - Siti Hasnah; Mijani Rahman; Abdur Rahman (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2019)
This study aims to determine the pollution levels of nitrate (N) and phosphate (P) in South Kalimantan Several subzone based method Pollution Index (Kep_MENLH /115/2003). The results were obtained relationship (r) between the variables Quality Standards(Y1) and variable (X) or Phosphate and Nitrate = 0.792. Calculation of the value of R2-determinant obtained yield was 0.672. This means that 67.2% factor Water QualityStandard (Y) is influenced by factors Phosphate and Nitrate, while the remaining 33.8%is influenced by other variables that can not be explained in the equation. The ratio between the parameter P and N (P = 0.577 N = 0,062 = 9.30), is between 7 to 12. It means that the variable Phosphate and Nitrate is not a limiting factor for contamination.Calculation results of the pollution index pareameter P and N obtained a value of 9.30,still meet quality standards for some sub-sub-basins (Riam Kanan, Tabanio, Naiyan River, River Satui, Kintap River, and the River Sebamban).